How geographic distance and political ideology interact to influence public perception of unconventional oil/natural gas development. (October 2016) - Clarke, Christopher E.; Bugden, Dylan; Hart, P. Sol; Stedman, Richard C.; Jacquet, Jeffrey B.; Evensen, Darrick T.N.; Boudet, Hilary S.
Abstract: A growing area of research has addressed public perception of unconventional oil and natural gas development via hydraulic fracturing ("fracking"). We extend this research by examining how geographic proximity to such extraction interacts with political ideology to influence issue support. Regression analysis of data from a fall 2013 national telephone survey of United States residents reveals that as respondents' geographic distance from areas experiencing significant development increases, political ideology becomes more strongly associated with issue support, with the liberal-partisan divide widening. Our findings support construal level theory's central premise: that people use more abstract considerations (like political ideology) the more geographically removed they are from an issue. We discuss implications for studying public opinion of energy development as well as for risk communication. Highlights: Conservatives support unconventional oil and gas development (UOGD) more than liberals. This divide widened as geographic distance from UOGD areas increased Construal Level Theory may help explain this finding We discuss implications for energy policy and risk communication